Identification of sequence elements contributing to the intrinsic curvature of the mouse satellite DNA repeat. - Carrera, P (1991)
In this paper, the contribution of different sequence elements to the intrisic curvature of the mouse satellite DNA repeat was investigated. This DNA fragment contains nineteen groups of three or more consecutive adenines which are only poorly phased with respect to the helical repeat. The mouse satellite DNA repeat shows a sinusoidal pattern of cleavage by the hydroxyl radical; the waves of reactivity are phased with respect to the A-tracts. Some interesting observations arise from a detailed analysis of these cleavage patterns: a) the maxima of hydroxyl radical cleavage are more periodically spaced along the DNA sequence than the A-tracts themselves. As a consequence, the position of each maximum with respect to the A-tract is variable; b) the sequence 5' TGGAATATG/AA 3' shows a sinusoidal pattern of hydroxyl radical cleavage. This sequence shows a retarded migration in polyacrylamide gels indicating that it is actually intrinsically curved. These results are discussed in view of the current models for DNA curvature.